2017
DOI: 10.1186/s12872-017-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 repletion versus placebo as adjunctive treatment of heart failure patient quality of life and hormonal indices: a randomized, double-blind, placebo-controlled trial

Abstract: BackgroundVitamin D status may influence heart failure (HF) patient outcomes by affecting b-type natriuretic peptide (BNP), parathyroid hormone (PTH), and enhancing cardiac contractility. Vitamin D deficiency is associated with morbidity and mortality in HF patients. The objective of this study was to determine if vitamin D3 at a comparatively high dose would replete 25-hydroxyvitamin D (25(OH)D) stores, improve BNP, PTH, cardiopulmonary function, reduce inflammatory markers, and improve quality of life (QOL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…Interestingly, a previous study suggested that vitamin D supplementation has great benefits as an anti-inflammatory agent in infants with chronic HF by helping acceleration of the clinical improvement and cytokine profile balance (43) . Previous studies found that vitamin D supplementation was significantly associated with better survival, specifically in patients with documented deficiency (14) , and vitamin D may be an important adjunct to standard HF therapy (44) and improve quality of life (QOL) (45) . In contrast, a study found that treatment with Vitamin D supplementation did not show clear evidence of benefit for preventing HF or influencing its clinical course (46) , while another study found that vitamin D supplementation has no beneficial effects on improvement of LV function and exercise tolerance in chronic HF patients (47) .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study suggested that vitamin D supplementation has great benefits as an anti-inflammatory agent in infants with chronic HF by helping acceleration of the clinical improvement and cytokine profile balance (43) . Previous studies found that vitamin D supplementation was significantly associated with better survival, specifically in patients with documented deficiency (14) , and vitamin D may be an important adjunct to standard HF therapy (44) and improve quality of life (QOL) (45) . In contrast, a study found that treatment with Vitamin D supplementation did not show clear evidence of benefit for preventing HF or influencing its clinical course (46) , while another study found that vitamin D supplementation has no beneficial effects on improvement of LV function and exercise tolerance in chronic HF patients (47) .…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that the same criteria can be named inclusion (patients with a particular disease are included) or exclusion criteria (patients without this particular disease are excluded) 6 7. Criteria should be specified as inclusion or exclusion 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Early trials of vitamin D supplementation in CHF were inconclusive possibly due to inclusion criteria, calciumbased placebo, dosing regimen, use of vitamin D 2 (rather than D 3 ) and heterogeneous CHF population [56][57][58], limiting their ability to provide clarity of benefit [25], whilst no trials have shown any adverse safety signals including up to 10,000 IU daily [59]. Recent meta-analyses have suggested that vitamin D might reduce inflammation (assessed by tumour necrosis factor-alpha levels (TNF-α) [60]), but that it is neutral for heart function [61].…”
Section: Vitamin D As An Interventionmentioning
confidence: 99%